Spatial patterns, factor identification, and ethnic differences: a study of traditional villages in the Yuan River Basin based on geographical detectors. - Ding, Chuanbiao; Zhao, Yongqi (Humanities & Social Sciences Communications, 2025)
The economic and cultural benefits of traditional Chinese villages are becoming increasingly apparent. Their spatial distribution characteristics play a significant role in promoting China's rural revitalization and reviving national culture. Our study selected 826 traditional villages in the Yuan River Basin (YRB) area and used the nearest neighbor index, geographical concentration, and kernel density estimation methods to reveal the spatial distribution pattern and the spatial distribution differences of said villages. We used a geodetector to quantify the natural, economic, and cultural factors influencing the spatial pattern of traditional villages and measured their interactions. The results showed that (1) the spatial distribution of traditional villages in the YRB is characterized by obvious regional and ethnic agglomerations, forming a spatial distribution pattern of "two nuclei, one belt, and many points". In terms of ethnicity, we found that the Han Chinese predominantly resided in the lowlands along the main valley of the Yuan River, while ethnic minorities inhabited both sides of the mountainous areas. (2) The number and proportion of minority populations, the proportion of primary industries, the slope of the terrain, the urbanization rate, and the proximity of water significantly influenced the spatial distribution of traditional villages in the YRB. These factors had different effects on different ethnic traditional villages, exacerbating the spatial agglomeration of each village. (3) Cross-detection revealed that the spatial distribution pattern of the YRB's traditional villages emerged through three phases: layout, evolution in distribution, and retention patterns, shaped by natural, economic, and social factors. Through this study, we were able to quantify the influences of the natural environment, the economy, and culture on the distribution of traditional villages. In uncovering the spatial distribution patterns of traditional villages and the characteristics of ethnic agglomeration at the watershed scale, we have laid the foundation for the scientific research and protection of traditional villages in multi-ethnic areas of the YRB.